2016
DOI: 10.1590/0001-3765201620160127
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Link between Apoptosis and Autophagy: a Promising New Role for RB

Abstract: Physiological processes, as autophagy, proliferation and apoptosis are affected during carcinogenesis.Restoring cellular sensitivity to apoptotic stimuli, such as the antineoplastic cocktails, has been explored as a strategy to eliminate cancer cells. Autophagy, a physiological process of recycling organelles and macromolecules can be deviated from homeostasis to support cancer cells survival, proliferation, escape from apoptosis, and therapy resistance. The relationship between autophagy and apoptosis is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 139 publications
1
25
0
Order By: Relevance
“…The regulation of autophagy on cell death is 2-fold: mild autophagy protects cells from harmful conditions and promotes cell survival; severe or rapid autophagy can induce programmed cell death, known as autophagic cell death (autophagy-mediated cell death, ACD). However, the regulation of apoptosis on cell death is unidirectional, and the defect of apoptosis will lead to the occurrence of tumor cell death (36)(37)(38)(39). Aspp2 induced apoptosis protein expression in Aspp2-ad and combination groups, Bax and activation of caspase-3 expression increased greatly both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of autophagy on cell death is 2-fold: mild autophagy protects cells from harmful conditions and promotes cell survival; severe or rapid autophagy can induce programmed cell death, known as autophagic cell death (autophagy-mediated cell death, ACD). However, the regulation of apoptosis on cell death is unidirectional, and the defect of apoptosis will lead to the occurrence of tumor cell death (36)(37)(38)(39). Aspp2 induced apoptosis protein expression in Aspp2-ad and combination groups, Bax and activation of caspase-3 expression increased greatly both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that the NRK-52E cells were treated with curcumin showed a significant activation of protective autophagy and upregulated the level of Beclin 1 and the ratio of LC3II and LC3I. Previous study found that curcumin could protect cells against oxidative stress-induced damage through inhibiting apoptosis and inducing autophagy ( 20 ). Our findings also confirm this conclusion.…”
Section: Discussionmentioning
confidence: 74%
“…Research on pRb shows that it plays a fundamental role in cell cycle mechanisms ( 35 ). pRb is obtained when the Rb is phosphorylated by CDKs ( 36 ), then it is able to release E2F.…”
Section: Discussionmentioning
confidence: 99%